PENGEMBANGAN E-MODUL PEMBELAJARAN TEKNIK INSTALASI TENAGA LISTRIK BERBASIS ANDROID DI SMK MEDAN - Mill Nanda; Hamonangan Tambunan (Universitas Negeri Medan, 2023)
Abstract The purpose of this study is to determine the process of making a good e-module, the feasibility of learning e-modules and the effectiveness of android-based learning e-modules in terms of student learning outcomes. This research was carried out on class X students of Electrical Power Installation Engineering at SMK Negeri 14 Medan in the odd semester of the 2022/2023 academic year. This research is a type of Research and Development (R&D) research using the ADDIE development model. The results of this study show that learning e-modules are very feasible to be used in learning. The results of the Indepentend sample t test analysis showed the results of t count Ëƒ ttable which is 7,392 > 2,048 and sig. (2-tailed) < 0.05 & 0.000 < 0.05, then the H a hypothesis is acceptable. Thus, it can be concluded that learning using android-based learning E-module is effective on student learning outcomes in the subject of basic electromechanical work class X Electrical Power Installation Engineering SMK Negeri 14 Medan..Â Key Words: E-module Learning, Feasibility, Effectiveness, Basic Electromechanical WorkÂ AbstrakThe purpose of this study is to determine the process of making a good e-module, the feasibility of learning e-modules and the effectiveness of android-based learning e-modules in terms of student learning outcomes. This research was carried out on class X students of Electrical Power Installation Engineering at SMK Negeri 14 Medan in the odd semester of the 2022/2023 academic year. This research is a type of Research and Development (R&D) research using the ADDIE development model. The results of this study show that learning e-modules are very feasible to be used in learning. The results of the Indepentend sample t test analysis showed the results of t count Ëƒ ttable which is 7,392 > 2,048 and sig. (2-tailed) < 0.05 & 0.000 < 0.05, then the H a hypothesis is acceptable. Thus, it can be concluded that learning using android-based learning E-module is effective on student learning outcomes in the subject of basic electromechanical work class X Electrical Power Installation Engineering SMK Negeri 14 Medan.Â Kata Kunci: E-modul Pembelajaran, Kelayakan, Efektivitas, Pekerjaan Dasar Elektromekanik